Family Involvement in Caring for Inpatients in Acute Care Hospital Settings: A Systematic Review of Literature - Elizabeth Gwaza PhD; Gladys Msiska (SAGE Publishing, 2022)
Family members, also known as patients' guardians (PG) are involved in caring for inpatients in acute care hospital settings. The practice is adopted from Family Centred Care (FCC) approach. This literature review aimed to provide an overview of key findings in literature on the practice of involving PGs in acute care hospital settings We used a systematic literature search to select original research articles or systematic reviews published in English between 2008 and 2019 that discussed PGs in acute care hospital settings. Studies that discussed PGs in long-term care hospital or in-home settings were excluded from this literature review. Literature was sought from CINAHL, MEDLINE, and PsycINFO. CASP and JBI checklist was used to appraise the full-text articles for inclusion in the literature review. Twenty-six articles were included. Findings show that there is limited literature on this topic although healthcare institutions involve PGs in their routine inpatient care. Three themes emerged from the review; the FCC approach, roles of PGs in acute care hospitals, and implications of involving PGs in acute care hospitals. PGs offer any care that is left undone by nurses in acute care hospitals to ensure that their patients' needs are met. However, their involvement is not consistent with FCC principles. This leads to physical, psychosocial, and economic implications for PGs. We recommend that nurse practitioners should consistently implement FCC principles to enable PGs to offer meaningful care to their inpatients.